2006
DOI: 10.1007/s10751-006-9313-6
|View full text |Cite
|
Sign up to set email alerts
|

Defects induced by electron irradiation in hollandite ceramics, specific radioactive cesium-host wasteforms: a 57Fe Mössbauer study

Abstract: Several single phase hollandite ceramics having Ba 2+ x Cs + y (C = Al,Fe) 3+ 2x+y Ti 4+ 8j2xjy O 16 composition have been synthesized and irradiated under external electron beams simulating the b-irradiation of radioactive cesium. These samples have been characterized by 57 Fe transmission Mö ssbauer spectroscopy. Mö ssbauer results show that the irradiation modifies the local arrangements of Ba cations around Fe 3+ ions by atomic displacement of Ba ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…12,13 . However, our results are somewhat in contrast to those reported by Nguyen et al (2005) who found that Fe 3+ occupied two distinct sites in ferric Ba-Cs hollandite structures (Ba1Cs0.28Al1.46Fe0.82Ti5.72O16, the most analogous to the compositions studied in this investigation and nominally identical to that studied by Leinekugel-le-Cocq et al) and that irradiation led to the formation of a distinct third site 11 . As the tetragonal space group only has one crystallographic site for framework B cations, it is possible to speculate that the pristine samples studied by Nguyen et al were either not single phase or possibly contaminated with other Fe bearing secondary phases.…”
Section: Mössbauer Spectroscopycontrasting
confidence: 99%
See 1 more Smart Citation
“…12,13 . However, our results are somewhat in contrast to those reported by Nguyen et al (2005) who found that Fe 3+ occupied two distinct sites in ferric Ba-Cs hollandite structures (Ba1Cs0.28Al1.46Fe0.82Ti5.72O16, the most analogous to the compositions studied in this investigation and nominally identical to that studied by Leinekugel-le-Cocq et al) and that irradiation led to the formation of a distinct third site 11 . As the tetragonal space group only has one crystallographic site for framework B cations, it is possible to speculate that the pristine samples studied by Nguyen et al were either not single phase or possibly contaminated with other Fe bearing secondary phases.…”
Section: Mössbauer Spectroscopycontrasting
confidence: 99%
“…Previous work has synthesised hollandites containing iron and caesium however, the influence of varying Cs content on the local Fe structural environment has not been investigated 2,9,[11][12][13] . This study was devised to investigate the stability of the structure, in particular Fe charge compensation, with respect to Cs substitution.…”
Section: Introductionmentioning
confidence: 99%
“…´quent, cette e ´tude RMN montre que les irradiations e ´lectroniques induisent la formation de lacunes d'oxyge `ne autour des ions Al 3þ de la hollandite. Cela est par ailleurs en accord avec les re ´sultats que nous avons obtenus par spectroscopie Mo ¨ssbauer du fer pour une hollandite Ba 1,16 Fe 2,32 Ti 5,68 O 16 irradie ´e [10,29].…”
Section: Modifications Structurales Induites Dans La Hollandite Par I...unclassified
“… Hollandite can be found in SYNROC C (a mutli-phase ceramic nuclear waste form) and serves as a host phase for radioactive Cs . The ability of this phase to accommodate Ba 2+ , Cs + , Rb + , and Sr 2+ into the crystallographic sites in this structure makes it applicable for the immobilization of 137 Cs. Barium titanate-type compounds that adopt the hollandite-type structure have also been proposed for use as oxidation catalysts, ion exchangers, solid ionic conductors, dielectric resonators, and battery materials. ,, …”
Section: Introductionmentioning
confidence: 99%